Human Understanding and God-talk in Jāmī and Beyond - Sami Muhammad (Open Theology)
This article explores ‘Abd al-Raḥmān al-Jāmī’s use of what I call “pictorial demonstration,” a method of solving philosophical problems by introducing pictorial rather than logical distinctions. It contrasts Jāmī’s integration of reason and imagination with the ratiocentrism of some medieval Islamic philosophers and modern analytic traditions, highlighting his use of the light analogy to solve some problems related to the Akbarian doctrine of waḥdat al-wujūd. By showing how Jāmī’s approach transcends the limits of rational argumentation, the article underscores the relevance of his thought to contemporary philosophical discussions on the interplay of reason, imagination, and the ineffable, offering insights into how premodern Islamic traditions can enrich modern philosophical discourse.